Consider this solution, if it is possible, check the result:
1) if to divide polynomial 'x³-3x²-6x+8' on 'x+2' result is: x²-5x+4, then x³-3x²-6x+8=(x+2)(x²-5x+4);
2) x²-5x+4=(x-1)(x-4), then
3) x³-3x²-6x+8=(x+2)(x-1)(x-4).
4) zeros are: -2;1;4. Other zeros are: 1 and 4.
Answer: 1;4.
Answer:
Roughly 70.29 degrees
Step-by-step explanation:
Equation:
(2x+27)+(2x-11)+3x = 180
7x + 16 = 180
7x = 164
x ~ 23.43
Angle C:
3x
3(23.43)
70.29
Maybe 50 divided by 25 is 2 so the answer is 2
hope i helped :D : D
-1.4, -1.25, 1/25 is the answer
Answer: x=−9/4
Step-by-step explanation:
Let's solve your equation step-by-step.
−2(x+14)+1=5
Step 1: Simplify both sides of the equation.
−2(x+14)+1=5(−2)(x)+(−2)(14)+1=5(Distribute)−2x+
−1
2
+1=5
(−2x)+(
−1
2
+1)=5(Combine Like Terms)
−2x+
1
2
=5
−2x+
1
2
=5
Step 2: Subtract 1/2 from both sides.
−2x+
1
2
−
1
2
=5−
1
2
−2x=
9
2
Step 3: Divide both sides by -2.
−2x
−2
=
9
2
−2
x=
−9
4